On the Use of Expectations Data in Estimating Structural Dynamic Choice Models - van der Klaauw, Wilbert (Journal of Labor Economics, 2012)
Despite the importance of expectations in models of decision behavior under uncertainty, few empirical economists have made use of subjective expectations data in estimating such models. Assuming that expectations about future behavior accurately portray optimal future behavior conditional on current information, it is shown that such data can provide similar information about the decision process as can data on current or retrospective behavior. The value of self-reported choice expectations is illustrated by using information on respondents’ expected future occupation in the estimation of a structural dynamic model of teacher career decisions under uncertainty.